Sistem Pengendali Pengambilan Gambar Pada Kamera DSLR Melalui Protokol PTP - Muhammad Iqbal; Triyogatama Wahyu Widodo; Bakhtiar Aldino Ardi Sumbodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
DSLR is a professional camera that uses a high-quality digital sensor with high image sharpness. This camera can use various lenses based on user needs. Taking pictures using a digital SLR camera is not an easy matter, the position of object, location, and intensity of light affect the resulting image. In this research, designed and built a system that can control the DSLR cameras via PTP protocol. Image capture is implemented using the USB Host Shield, which is a tool that is used as a connector between a DSLR camera with an Arduino as a controller.  Results of this research is a tool that is capable of taking pictures on the object by sending instructions via existing command on the Arduino serial monitor. The system test is done by testing image capturing through the PTP protocol, the change of the camera position, the influence of the camera's sensitivity to light, as well as the influence of light intensity. The result is DSLR cameras via PTP protocol can take a picture, adjust the position, adjust the ISO in accordance with the needs of the object, and set the white balance according to the location where the image capturing done.